Students’ Knowledge and Attitudes toward Science: Its Correlation on Students’ Disbelief in Non-Scientific Misinformation - Rofieq, A.; Fauzi, A. (Jurnal Pendidikan IPA Indonesia, 2022)
Immense students’ belief in misinformation indicates the less optimized quality of science education. However, research that analyzes the predictors of this problem is still rarely done. Biology knowledge (BK) depicts the level of biological information mastered by students; attitude toward science (ATS) is related to students' views when participating in science learning; while disbelief in conspiracy theories (DiCT) describes a person's ability to examine information that contradicts scientific truth. The current research was aimed at analyzing BK, ATS, and DiCT among Biology students, as well as the correlation between the three. The data collection instrument used was an online questionnaire comprising four main sections: demographic items, 15 Biology, and the General Public Questionnaire items, 40 ATS test items, and 8 DiCT items. Analysis was conducted on data from 820 respondents collected from February-March 2022. Some techniques for data analysis were applied, including frequency and percentage estimation, Kruskal-Wallis H test analysis, Dunn's test analysis, Kendall's Tau Correlation, and rank-based estimation regression. This research found that: 1) student’s ages and genders did not significantly contribute to any, while institutional status and study years did to BK and DiCT; 2) study program significantly contributed to ATS, and 3) ATS was found to not correlate significantly with DiCT, but BK was significant by the DiCT. Therefore, BK becomes the main competency that can protect students from unscientific conspiracy theories. This study has revealed a novelty framework about the position of knowledge and attitude in predicting students' abilities when examining misinformation.